Green synthesis of zinc nanoparticles from Rhizophora apiculata and its characterisation and biological property ( antibacterial) - Preethi Raj M; Dr. S. Rajeshkumar (Revista Electronica de Veterinaria)
The emergence of multidrug-resistant pathogens has necessitated the development of novel antibacterial agents, with nanoparticles emerging as promising nanoantibiotics due to their unique physicochemical properties. This study reports the green synthesis, characterization, and antibacterial evaluation of zinc oxide nanoparticles (ZnO NPs) fabricated using the aqueous leaf extract of Rhizophora apiculata, a tannin-rich mangrove plant. The phytochemical profile of the extract was analyzed, confirming the presence of tannins, flavonoids, and reducing sugars that function as effective reducing and capping agents. The biosynthesis was optimized by varying precursor concentration (0.1–0.4 M zinc acetate), pH (6–10), temperature (40–80°C), and reaction time (1–4 hours), with optimal conditions identified at 0.2 M precursor concentration, pH 8, 70°C, and 2 hours reaction time. The synthesized nanoparticles were characterized using UV-Vis spectroscopy (surface plasmon resonance peak at 368 nm), Fourier-transform infrared spectroscopy (confirming Zn-O stretching at 532 cm⁻¹ and phytochemical capping), X-ray diffraction (hexagonal wurtzite structure with average crystallite size of 28.4 nm), scanning electron microscopy (spherical to irregular morphology with some agglomeration), energy-dispersive X-ray spectroscopy (elemental composition confirming Zn and O), dynamic light scattering (average hydrodynamic size 86.7 nm, polydispersity index 0.284), and zeta potential analysis (−24.6 mV indicating good stability). Thermogravimetric analysis demonstrated thermal stability up to 400°C with 18% weight loss attributed to phytochemical decomposition. The antibacterial activity was evaluated against clinically significant pathogens using agar well diffusion and broth microdilution methods. ZnO NPs exhibited concentration-dependent inhibition against both Gram-positive (Staphylococcus aureus MTCC 96, Bacillus subtilis MTCC 121) and Gram-negative (Escherichia coli MTCC 43, Pseudomonas aeruginosa MTCC 424, Klebsiella pneumoniae MTCC 109) bacteria. The minimum inhibitory concentration ranged from 31.25 to 125 μg/mL, with S. aureus showing the highest susceptibility (MIC 31.25 μg/mL, zone of inhibition 21.4 ± 1.2 mm at 250 μg/mL). Time-kill kinetics revealed bactericidal activity within 6–8 hours of exposure. Mechanistic studies using reactive oxygen species assays and membrane permeability analysis confirmed nanoparticle-induced oxidative stress and membrane disruption as primary antibacterial mechanisms. This study demonstrates that R. apiculata-mediated ZnO NPs possess significant antibacterial potential, offering an eco-friendly approach for developing effective nanoantibiotics against drug-resistant pathogens.